Comparison of recovery and immunochemical detection of peanut proteins from differentially roasted peanut flour using ELISA. (15th September 2019) - Jayasena, Shyamali; Koppelman, Stef J.; Nayak, Balunkeswar; Taylor, Steve L.; Baumert, Joseph L.
Highlights: Most ELISA kits perform well in detecting peanut from minimally roasted peanut flours. Most commercial peanut ELISAs are unable to quantify peanut in dark roast peanut flours at ≤25 ppm. ELISAs underestimate protein content due to reduced solubility & heat induced changes in proteins. Only the Morinaga kit had sufficient sensitivity to detect peanut at low concentrations of dark roast peanut flours. Abstract: The effect of heat on extractability and immunoreactivity of proteins from roasted peanut flours and whole peanuts was evaluated using two general protein assays and six commercial peanut ELISA kits, respectively. The highest amount of protein was recovered from roasted peanuts with all ELISAs, while recovery showed a decrease with increasing levels of roasting of the peanut flours. Only the Morinaga kit showed sufficient sensitivity to detect peanut at low concentrations of the dark roast peanut flours. Both the protein and immunoassays indicated a decrease in protein solubility with roasting. The underestimation by immunoassays is a combination of decreased solubility and heat induced changes in the proteins that are being targeted by the ELISA antibodies. These findings suggest that most commercial ELISA kits may not reliably quantify peanut present in dark roast peanut flours at ≤25 ppm.